2012
DOI: 10.3233/wor-2012-0587-3227
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and detachment between shifts, and fatigue during a twelve-hour shift

Abstract: The study investigated the role of recovery and detachment in the break period between two shifts for fatigue in the current shift. A time-based paper-and-pencil diary study was carried out observing sixty-four railway controllers over ten consecutive working shifts. The results demonstrated that fatigue in the current shift was not only affected by recovery and psychological detachment during break phases before a shift, but also by fatigue at shift onset and perceived workload during the shift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
4
18
0
Order By: Relevance
“…Seventeen studies reported the effects of work demand factors on fatigue. Among these studies, nine longitudinal/process studies investigated the length of work time, with seven focusing on train drivers (McGuffog et al, 2004 ; Darwent et al, 2008 ; Dorrian et al, 2008 ; Prakash et al, 2011 ; Cabonl et al, 2012 ; Robertson et al, 2013 ; Kazemi et al, 2016 ), and two on controllers (Popkin et al, 2001 ; Korunka et al, 2012 ). Overall, no matter whether in passenger or freight train operating companies, the train drivers working longer hours had higher fatigue scores than those working fewer hours.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seventeen studies reported the effects of work demand factors on fatigue. Among these studies, nine longitudinal/process studies investigated the length of work time, with seven focusing on train drivers (McGuffog et al, 2004 ; Darwent et al, 2008 ; Dorrian et al, 2008 ; Prakash et al, 2011 ; Cabonl et al, 2012 ; Robertson et al, 2013 ; Kazemi et al, 2016 ), and two on controllers (Popkin et al, 2001 ; Korunka et al, 2012 ). Overall, no matter whether in passenger or freight train operating companies, the train drivers working longer hours had higher fatigue scores than those working fewer hours.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three studies investigated the effect of time into the work period and the differences between night shifts and day shifts. Among these, six were cross-sectional mail surveys (Kibblewhite, 2003 ; Ku and Smith, 2010 ; Zoer et al, 2011 ; Zimmermann et al, 2015 ; Cotrim et al, 2017 ; Fan and Smith, 2017 ), and 17 were longitudinal/process studies (Popkin et al, 2001 ; Roach et al, 2001 ; Harma et al, 2002 ; McGuffog et al, 2004 ; Dorrian et al, 2006 , 2007a , 2008 , 2011 ; Darwent et al, 2008 , 2015 ; Jay et al, 2008 ; Cabonl et al, 2012 ; Korunka et al, 2012 ; Paterson et al, 2012 ; Cebola et al, 2013 ; de Araújo Fernandes et al, 2013 ; Robertson et al, 2013 ). Most of these studies showed that night shifts result in fatigue (e.g., Dorrian et al, 2011 ), as well as sleepiness and cumulative sleep loss (Darwent et al, 2008 ; Cotrim et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations